Sexual network characteristics and partnership types among men who have sex with men diagnosed with syphilis, gonorrhoea and/or chlamydia in Lima, Peru - Freese, Jonathan (2023)
Objectives Sexual networks are known to structure sexually transmitted infection (STI) transmission among men who have sex with men (MSM). We sought to estimate the risks of STI diagnosis for various partnership types within these networks. Methods Our cross-sectional survey analysed data from 1376 MSM screened for a partner management intervention in Lima, Peru. Participants were tested for HIV, syphilis, gonorrhoea (NG) and chlamydia (CT) and completed surveys on their demographics, sexual identity/role, HIV status, partnership types and sexual network from the prior 90 days. χ2 and Wilcoxon rank-sum tests compared participants without an STI to those diagnosed with (1) syphilis, (2) NG and/or CT (NG/CT) and (3) syphilis and NG/CT coinfection (coinfection). Results 40.8% (n=561/1376) of participants were diagnosed with an STI (syphilis: 14.9%, NG/CT: 16.4%, coinfection: 9.5%). 47.9% of all participants were living with HIV and 8.9% were newly diagnosed. A greater proportion of participants with syphilis and coinfection were living with HIV (73.5%, p<0.001; 71.0%, p<0.001) compared with those with NG/CT (47.8%) or no STI (37.8%). Participants with syphilis more often reported sex-on-premises venues (SOPVs) as the location of their last sexual encounter (51.7%, p=0.038) while those with NG/CT tended to meet their last sexual partner online (72.8%, p=0.031). Respondents with coinfection were the only STI group more likely to report transactional sex than participants without an STI (31.3%, p=0.039). Conclusions Sexual networks and partnership types of Peruvian MSM are associated with differential risks for STIs. Participants diagnosed with syphilis tended to meet single-encounter casual partners at SOPV, while MSM with NG/CT were younger and often contacted casual partners online. Coinfection had higher frequency of transactional sex. These findings suggest the potential importance of public health interventions through combined syphilis/HIV screening at SOPV, syphilis screening at routine clinic appointments for MSM living with HIV and directed advertisements and/or access to NG/CT testing through online platforms.